2022
DOI: 10.3390/diagnostics12112627
|View full text |Cite
|
Sign up to set email alerts
|

Physics Informed Neural Networks (PINN) for Low Snr Magnetic Resonance Electrical Properties Tomography (MREPT)

Abstract: Electrical properties (EPs) of tissues facilitate early detection of cancerous tissues. Magnetic resonance electrical properties tomography (MREPT) is a technique to non-invasively probe the EPs of tissues from MRI measurements. Most MREPT methods rely on numerical differentiation (ND) to solve partial differential Equations (PDEs) to reconstruct the EPs. However, they are not practical for clinical data because ND is noise sensitive and the MRI measurements for MREPT are noisy in nature. Recently, Physics inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Our method can directly reconstruct the EPs from noisy measurements, unlike previous supervised deep learning-based EPT methods [31]- [34], [36] that require a large amount of known data pairs to supervise the training. Compared with previous hybrid deep learning EPT methods [37], [38] which combine deep learning and CR-EPT to solve EP from convection-reaction equations, our method directly trains a neural network (EP Net) to represent the EPs based on measured data and the Helmholtz PDE without requiring any boundary conditions and hyperparameter tuning for the diffusion coefficient. Finally, we observed that PIFON-EPT would always de-noise and reconstruct the B + 1 values first before the EP reconstruction, as shown in the red dotted box of Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our method can directly reconstruct the EPs from noisy measurements, unlike previous supervised deep learning-based EPT methods [31]- [34], [36] that require a large amount of known data pairs to supervise the training. Compared with previous hybrid deep learning EPT methods [37], [38] which combine deep learning and CR-EPT to solve EP from convection-reaction equations, our method directly trains a neural network (EP Net) to represent the EPs based on measured data and the Helmholtz PDE without requiring any boundary conditions and hyperparameter tuning for the diffusion coefficient. Finally, we observed that PIFON-EPT would always de-noise and reconstruct the B + 1 values first before the EP reconstruction, as shown in the red dotted box of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These hybrid methods offer a better generalization, however, repeated electromagnetic simulations are still required to generate training data, which can be very expensive and time-consuming. Another hybrid deep learning EPT method was proposed to directly reconstruct conductivity from input transceive phases [38]. Precisely, a neural network is trained to represent the input transceive phase map, where the gradients of the phase are computed by automatic differentiation [39] and then used to solve the phase-only convectionreaction EPT.…”
mentioning
confidence: 99%
“…PINNs have already been used in fields such as biochemistry [40], hydrogeology [41], and astronomy [42]. They are also frequently used to solve ordinary and partial differential equations [43,44]. However, PINNs have not yet been applied to the conceptual Koren-Feingold model, which consists of nonlinear delayed differential equations.…”
Section: Artificial Neural Network and Physics-informed Neural Networkmentioning
confidence: 99%
“…Therefore, the development of new sensing technologies is needed, such as sensing materials for detection. In the past, conductive tissue-like phantoms had been used to measure the thermal effects of electromagnetic exposure [15,16], evaluation of medical imaging techniques [17,18], conductivity influence in electrical stimulation [19][20][21], that can mimic the tissue hardness [22], but it has not been reported as a sensing material for 3D localization.…”
Section: Introductionmentioning
confidence: 99%